HMG-CoA reductase inhibitor rosuvastatin improves abnormal brain electrical activity via mechanisms involving eNOS. (22nd January 2015) - Seker, F.B.; Kilic, U.; Caglayan, B.; Ethemoglu, M.S.; Caglayan, A.B.; Ekimci, N.; Demirci, S.; Dogan, A.; Oztezcan, S.; Sahin, F.; Yilmaz, B.; Kilic, E.
Highlights: We evaluated the role of rosuvastatin on brain electrical activity for the first time. The mechanism of antiepileptic activity of rosuvastatin relies on the activity of eNOS. We compared anti-epileptic effects of HMG-CoA reductase inhibitors. We report that epilepsy increases BBB permeability and rosuvastatin reverses it. We report gene expression profiling under effect of HMG-CoA reductase- and eNOS inhibitor. Abstract: Apart from its repressing effect on plasma lipid levels, 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase inhibitors exert neuroprotective functions in animal models of neurodegenerative disorders. In view of these promising observations, we were interested in whether HMG-CoA reductase inhibition would affect epileptiform activity in the brain. To elucidate this issue, atorvastatin, simvastatin and rosuvastatin were administered orally at a dose of 20 mg/kg each for 3 days and their anti-epileptic activities were tested and compared in rats. Epileptiform activity in the brain was induced by an intracortical penicillin G injection. Among HMG-CoA reductase inhibitors, simvastatin-treatment was less effective in terms of spike frequency as compared with atorvastatin- and rosuvastatin-treated animals. Atorvastatin treatment reduced spike frequencies and amplitudes significantly throughout the experiment. However, the most pronounced anti-epileptic effect was observed in rosuvastatin-treated animals, which was associated with improved blood–brain barrier (BBB) integrity, increased expression of endothelial nitric oxide synthase (eNOS) mRNA and decreased expressions of pro-apoptotic p53, Bax and caspase-3 mRNAs. Inhibition of eNOS activity with l -NG-Nitroarginine Methyl Ester (l -NAME) reversed the anti-epileptic effect of rosuvastatin significantly. However, l -NAME did not alter the effect of rosuvastatin on the levels of p53, Bax and caspase-3 mRNA expression. Here, we provide evidence that among HMG-CoA reductase inhibitors, rosuvastatin was the most effective statin on the reduction of epileptiform activity, which was associated with improved BBB permeability, increased expression of eNOS and decreased expressions of pro-apoptotic p53, Bax and caspase-3. Our observation also revealed that the anti-epileptic effect of rosuvastatin was dependent on the increased expression level of eNOS. The robust anti-epileptic effect encourages proof-of-concept studies with rosuvastatin in human epilepsy patients with hypercholesterolemia.